Relationship Between Parenting Style and Establishment of Religious Characters at Taman Pendidikan Alquran (TPA) Masjid Alfurqon Desa Sikuliek Kecataman Koto Tangah Kota Padang - Gilang Ariesta Guchi; Vevi Sunarti (Universitas Negeri Padang, 2021)
This research was motivated by the low religious character of children studying at the Al-Furqon Mosque Education Park (TPA), Sikuliek Village, Koto Tangah District, Padang City. This is most likely due to ineffective and inaccurate parenting parents, which have a negative impact on the child's personality, especially in the development of religious character. Based on this phenomenon, the aim of this study is to describe the parenting parents of the parents in relation to the child, to describe the religious character of the child, and to determine the relationship between the parenting parentsof the parents and the development of the religious character of the child. Correlational quantitative analysis is the term for this form of study. All children who learned the Koran at the Al-Furqon Mosque Education Park were included in this report (TPA). Saturated samples were used as a sampling method. A questionnaire is the data collection method, and a list of statements is the data collection tool. The percentage formula and sperman rho were used in the data analysis technique. The results showed that low parenting parent, low religious character of children and there is a significant relationship between parenting parentswith the formation of children's religious character. Suggestions in this study are that parents are expected to be able to choose and sort out what parenting parents to apply to children, pay more attention to children and become role models for their children because the family environment is very much determined by the formation of children's religious character and the existence of cooperation between parents and administrators TPA to participate in motivating children to continuously attend lessons at the TPA so as to maximize the formation of children's religious character.Keywords: Parenting Parents, Religious Character